Safety and Feasibility of Microwave Ablation for Hepatocellular Carcinomas in the Elderly: A Systematic Review - Liang, Weiren; Hao, Weiyuan; Shao, Guoliang; Zheng, Jiaping; Zeng, Hui; Zhou, Danping; Yao, Hefeng (Frontiers in Oncology, 2022)
Background: Microwave ablation (MWA) of hepatocellular carcinomas (HCC) in the elderly has been the subject of new research in recent years. However, there is currently no strong data for the prognosis following MWA treatment for HCC in the elderly. Therefore, we conducted a systematic review to assess the safety and feasibility of MWA of HCC in elderly patients. Methods: Up until August 15, 2021, a comprehensive literature search was undertaken in PubMed, Scopus, CENTRAL (Cochrane Central Register of Controlled Trials), and Google Scholar databases for all published articles. Observational studies reporting the safety and feasibility of MWA for HCC in elderly patients were included. The Newcastle–Ottawa (NOS) scale was used to measure the quality assessment. Results: Our review, comprised of 7 observational studies, including a total of 7,683 HCC patients, looked at the safety and feasibility of MWA of HCC. Current evidence on the risks and outcomes of MWA of HCC treatments in elderly patients are discussed. Conclusions: According to our findings, elderly patients, even those with a high comorbidity index, benefited from MWA of HCC similar to younger patients. More clinical data is needed to determine selection criteria for elderly HCC patients to increase the possibility of receiving MWA as a potential lifesaving option. As such, further studies evaluating the outcomes of MWA for HCC treatment modalities in elderly patients are warranted.